Interactive Learning Methods to Increase Students' Motivation in Learning English: Students' Point of View - Radiana Andi Syahrir; Puspa Sari; Husnani Aliyah (Universitas Islam Negeri Palopo, 2025)
Interactive learning methods are one of the alternative learning models that help students express their curiosity and understand the knowledge or concepts they are studying. Emphasis on interactive learning methods is very important to increase student engagement and motivation, especially in learning English in junior high schools. Learning motivation is an important factor that influences students' success in mastering a foreign language. This study aims to determine the effectiveness of interactive learning methods in increasing students' motivation and interest in learning English. The method used in this study is descriptive qualitative with the research subjects being class VIIA. Data collection techniques include observation and interviews to explore students' perceptions regarding their experiences during English learning with interactive methods, such as group discussions, educational games, presentations, and technology-based learning media. The results showed that most students responded positively to the use of interactive methods, because it made the learning process more enjoyable, easier to understand, increased self-confidence, trained public speaking, and encouraged active involvement in class. However, some students also conveyed shortcomings, such as the existence of technology so that they rely on the internet to find answers and the interest in book literacy and students decreased. These findings indicate that interactive learning methods can be an effective strategy to increase motivation to learn English, provided that careful planning and adjustments are needed to meet students' needs.